THE ROLE OF ARTIFICIAL INTELLIGENCE (AI) AT SCHOOL LEARNING - Aristanto Aristanto; Eka Supriatna; Hanna Maria Panggabean; Eka Apriyanti; Hartini Hartini; Nur Indah Sari; Wahyu Kurniawati (Consilium: Education and Counseling Journal, 2023)
Services using AI can be found everywhere, such as Google Assistant, Siri, Google Translate, Computer Games, and so on. The purpose of this research is to find out the role of Artificial Intelligence (AI) in learning in schools. This research uses a descriptive qualitative approach with the literature study method. Sources of data were obtained through research journal articles, proceeding articles and books that were relevant to the research objectives. The results of this study found that AI can assist in analyzing individual student data and produce learning recommendations that are tailored to the needs and abilities of each student. Thus, AI can help teachers to provide a more personal and effective approach to the learning process. Adaptable Teaching: AI can be used to develop adaptive teaching systems, where learning materials can be adapted to students' level of understanding. For example, AI can provide additional exercises or additional explanatory material to students who are having difficulty understanding a particular topic